Evaluasi Efek Samping Penggunaan Obat Kombinasi Metformin dan Glimepiride pada Pasien Diabetes Melitus Tipe 2 - Ni Nyoman Wahyu Udayani; I Gusti Agung Ayu Kusuma Wardani; I Dewa Ayu Anom Yustari Nida (Jurnal Ilmiah Medicamento, 2022)
The combination of metformin and glimepiride can significantly reduce fasting blood glucose, post prandial blood glucose, and HbA1c levels. Side effects that often occur in the use of metformin are gastrointestinal disturbances. This study aims to determine the side effects of using a combination of metformin and glimepiride in outpatient type 2 diabetes mellitus at a hospital in Gianyar. This research is an observational research and data collection is done with a cross sectional approach and analyzed using descriptive methods. Data was taken by looking at the patient's medical record, including name, medical record number, gender, age, drugs given, patient diagnosis, and patient complaints during therapy. Sampling used purposive sampling technique with a total of 70 patients who entered the inclusion criteria. The results show that the number of women (62.86%). The most age range suffering from type 2 diabetes mellitus is 56-65 years (52.86%). The highest percentage of people with type 2 diabetes mellitus had a basic education level (40.00%). The side effects obtained from the combination of metformin and glimepiride in patients with type 2 diabetes mellitus at the hospital were nausea and vomiting (31.43%), flatulence (25.71%), fatigue (17.14%), headache (15.72%), and hypoglycemia (10.00%).